Identification of the long non-coding RNA H19 in plasma as a novel biomarker for diagnosis of gastric cancer - Zhou, Xiaoying; Yin, Chengqiang; Dang, Yini; Ye, Feng; Zhang, Guoxin (Scientific reports, 2015)
Recent studies have demonstrated that long non-coding RNAs (lncRNAs) are regarded as useful tools for cancer detection, particularly for the early stage; however, little is known about their diagnostic impact on gastric cancer (GC). We hypothesized that GC-related lncRNAs might release into the circulation during tumor initiation and could be utilized to detect and monitor GC. 8 lncRNAs which previously found to be differently expressed in GC were selected as candidate targets for subsequent circulating lncRNA assay. After validating in 20 pairs of tissues and plasma in training set, H19 was selected for further analysis in another 70 patients and 70 controls. Plasma level of H19 was significantly higher in GC patients compared with normal controls (p < 0.0001). By receiver operating characteristic curve (ROC) analysis, the area under the ROC curve (AUC) was 0.838; p < 0.001; sensitivity, 82.9%; specificity, 72.9%). Furthermore, H19 expression enabled the differentiation of early stage GC from controls with AUC of 0.877; sensitivity, 85.5%; specificity, 80.1%. Besides, plasma levels of H19 were significantly lower in postoperative samples than preoperative samples (p = 0.001). In conclusion, plasma H19 could serve as a potential biomarker for diagnosis of GC, in particular for early tumor screening.